THE EFFECT OF KCN ON GOLD ADSORPTION FROM HCl SOLUTION BY SYNTHESIZED MAGNETIC ACTIVATED CARBON COMPOSITE FROM IRON SAND - RIDWAN RIDWAN (Indonesian Mining Journal, 2012)
The composites of magnetic activated carbon has been successfully synthesized by utilizing the available materi- als abundant in the country such as iron sand, and other chemicals which are easily procured in local markets at low prices. The phase identifi cation using X-ray diffraction technique showed that the magnetic part is Fe3O4 with crystallite size about 30 nm. The effectiveness of gold absorption from chloride solution by activated carbon magnetic composites are close to 100% and showed very dependent on pH. An addition of KCN in to the gold chloride solution can reduce effectiveness of activated carbon to adsorb gold by up to 20%. These might be caused by the formation of Au(CN)2-, in the solution, which could change the mechanism of adsorption of gold by the activated carbon. Based on these experimental results, by using chloride it is possible to recover valuable minerals from the ore processing of mining, which are economically,as well as environment friendly and safe.